Trachyspermum ammi aromatic water: A traditional drink with considerable anti-Candida activity - Ali Arabi Monfared; Seyyed Amin Ayatolahi Mousavi; Kamiar Zomorodian; Davood Mehrabani; Aida Iraji; Mahmood Reza Moein (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Aromatic waters (AWs) are therapeutic distillates, which harbor both essential oil and water-soluble components of a plant. Due to the dispersion of the light amount of essence through the AWs, they have their specific pleasant smell, taste, and medicinal properties. In Iranian traditional medicine, Trachyspermum ammi AW is used to treat gastrointestinal disorders. The present study was conducted to determine the chemical composition of the essential oil extracted from T. ammi AW and its antifungal activities against Candida species. Materials and Methods: The composition of the essential oil extracted from T. ammi AW was analyzed by gas chromatography-mass spectrometry. In addition, the evaluation of the antifungal activity of AW against Candida species was performed using broth microdilution methods as recommended by the Clinical Laboratory Standard Institute. Moreover, the biofilm formation inhibition, antioxidant properties, and experimental activity of AW were determined in an animal model. Results: According to the results, thymol (78.08%) was the major compound of EO, followed by carvacrol (8.20%) and carvotanacetone (6.50%). Furthermore, T. ammi AW exhibited antifungal activities against the examined fungi and inhibited the biofilm formation of C. albicans at a concentration of up to 0.25 V/V. Histopathological analyses revealed that Candida colonization declined in the mice following the administration of T. ammi AW in a therapeutic trial. Conclusion: It seems that the presence of phenolic monoterpenes in AW has resulted in antifungal effects. Pleasant odor and antioxidant properties are extra bonuses to the antimicrobial effects of this plant. Based on the findings, AW might have the potential to be used in the management of alimentary candidiasis or oral hygienic products.